Role of Modern Technology in Teaching and Learning the English Language in Indian Educational Institutions - Sinha, Kanhaiya Kumar (Indonesian Journal of English Language Studies (IJELS), 2022)
The area of language schooling is converting at an ever-growing rate. Traditional notions of schooling are giving way to newer, greater modern approaches to considering how we analyze, accumulate information, and educate. The study room surroundings these days are absolutely one of a different kind from the conventional ones. The conventional strategies that are especially primarily based totally on lecturing and rote studying lessen English language studying to mechanical memorization and miserably fail in growing the English language as an ability for most of the newcomers. In an age of ubiquitous presence of technology, the pedagogy of coaching method has additionally passed through a sea-change. New technologies, just like the Internet, YouTube, Skype, Twitter, Blogs, etc., have brought the best stimulus and additionally, newcomers’ engagement and proper interactivity in the classrooms. But instructors’ burnout is an unhappy phenomenon that is affecting the coaching career in a whole lot of approaches. As we recognize, whiners don’t encourage others or mobilize them to act. Learning via way of means of instance, greater than ever, is the process of a trainee in the twenty-first century. Teachers, via the usage of the modern ELT (English Language Teaching) strategies like English songs, film clippings, dramatics, advertisements, sports activities, commentaries and plenty of greater values, can have interaction with the newcomers to come to be professionals in the English language. This paper specializes in the want to make English language coaching smooth and exciting through modern strategies.